The impact of EU data regulations on innovation, competitiveness, and growth: How can their Quality and capability be improved? - Bertin Martens (EconPol Forum, 2024)
Current EU data market regulation is fragmented and fails to realize the full social value of data. Economies of scope in the reuse and aggregation of non-rival data, together with transaction costs, are the main sources of market failures. The European Health Data Space offers an almost perfect data governance template. The General Data Protection Regulation and the Data Act fall short of this standard. Where feasible, the tension between private and social value of data can be bridged by private incentives to share. If not, mandatory sharing conditions will be applicable.
Keywords: 330